Microwave multi-stage countercurrent extraction of dihydromyricetin from Ampelopsis grossedentata - Li, Wei, biotehnolog (Array, 2007)
Microwave-assisted extraction (MAE) technique in combination with multi-stage countercurrent extraction (MCE), namely microwave multi-stage countercurrent extraction (MMCE), was evaluated for the extraction of dihydromyricetin (DMY) from Ampelopsis grossedentata. Ethanol, methanol and water were used as extract solvents in the MMCE method. Of the three solvents used, water was found to be the best in extracting DMY from Ampelopsis grossedentata because it had a good extraction yield and is inexpensive, non-toxic and environmentally friendly. The optimal conditions of MMCE for the extraction of DMY can be determined to be the ratio of the extraction solvent to plant material of 30:1, the extraction time of 5 min, the extraction temperature of 110 °C and the microwave power of 600 W. In addition, the extraction efficiency of the MMCE method was compared with that of the microwave static batch extraction (MSBE) under the optimum extraction conditions. It was found that the MMCE method offered higher extraction efficiency than the MSBE method. Thus, the study suggests that the MMCE method provides an alternative technique in terms of both cost and efficiency